ICHKI ISHLAR ORGANLARI NAVBATCHILIK QISMLARI FAOLIYATIDA RAQAMLASHTIRISHNING AHAMIYATI - Baratov Asadbek Ahadilla o‘g‘li, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article examines the issues of improving the work of duty units of internal affairs bodies (IAB). IAB duty units perform critical tasks such as public safety, crime prevention, and rapid response. The article suggests implementation of modern technologies, improvement of staff skills, effective communication with citizens and planning processes. The results of the analysis determine the necessary measures to improve the efficiency of the duty units and are important in strengthening public confidence. These recommendations serve to improve the quality of IAB activities and help to further strengthen public safety.